Pattern reconfigurable ESPAR antenna for vehicle‐to‐vehicle communications. Issue 3 (11th January 2018) - Marantis, Leonidas; Rongas, Dimitrios; Paraskevopoulos, Anastasios; Oikonomopoulos‐Zachos, Christos; Kanatas, Athanasios
Abstract : This study proposes an electronically switched parasitic array radiator (ESPAR) antenna at 5.9 GHz to meet the intelligent transportation systems standards. This antenna offers pattern switching capability with three distinct radiation patterns, i.e. one quasi‐omni and two directives in opposite directions, by controlling the mutual coupling at the parasitic elements with PIN diode switches. A considerable gain increase of up to 3 dB is achieved in the directive mode, while maintaining a satisfying impedance matching between the switching states. The compact ESPAR antenna is printed on a low loss Rogers dielectric and consists of one active and two parasitic monopoles. S 11 and radiation pattern results are presented, derived from both simulations and measurements, exhibiting a close agreement.